Design and Control of a Powered Hip Exoskeleton for Walking Assistance. (10th March 2015) - Wu, Qingcong; Wang, Xingsong; Du, Fengpo; Zhang, Xiaobo
The wearable powered exoskeleton is a human-robot cooperation system that integrates the strength of a robot with human intelligence. This paper presents the research results into a powered hip exoskeleton (PH-EXOS) designed to provide locomotive assistance to individuals with walking impediments. The Bowden cable actuated exoskeleton has an anthropomorphic structure with six degrees of freedom (DOF) in order to match the human hip anatomy and enable natural interaction with the user. The mechanical structure, the actuation system, and the interaction kinematics of PH-EXOS are optimized to achieve preferable manoeuvrability and harmony. For the control of the exoskeleton, a real-time control system is established in xPC target environment based on Matlab/RTW. A Cascaded PID controller is developed to perform the trajectories tracking tasks in passive control mode. Besides, based on the pressure information on the thigh, a fuzzy adaptive controller is developed to perform walking assistance tasks in active control mode. Preliminary treadmill walking experiments on a healthy subject were conducted to verify the effectiveness of the proposed device and control approaches in reducing walking effort.